The measurement of the fast neutron energy spectrum by using a He-3 proportional counter and the time-of-flight technique - (:unkn) unknown (My University, 1999)
Bu çalışmada 9Be$(3He,n)^{11}$C reaksiyonundan elde edilen hızlı nötronların spektrumunu ölçmek için bir teşebbüste bulunulmuştur. 1,52 m Nuffield siklotronunda 3 mm lik kalın Berilyum hedef 30 MeV lik He-3 iyonları ile bombardıman edilerek hızlı nötronlar üretilmiştir. Nötron spektrumlarmı ölçmek için bir He-3 orantılı sayıcı ve time-of-flight tekniği kullanılmıştır. Sıfır derecede (0°) nötronların 36,5 MeV ye kadar olmak üzere devamlı bir enerji dağılımında oldukları bulunmuştur.

In this study an attempt has been made to measure the fast neutron energy spectrum from the 9Be$(3He,n)^{11}$C reaction. The fast neutrons are produced by bombarding 3 mn thick Beryllium target with 30 MeV He-3 ions from the 1. 52 m Nuffield cyclotron. For the measurement of neutrons spectra, a He-3 proportional counter and the time-of-flight technique have been used. It was found that the neutrons at 0° have a continuous distribution of energies up to about 36,5 MeV.
Keywords: Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme